Malaria case management over 15 years (2006–2021) in Jakiri North-West Region Cameroon - Ndang, Ndong Henry; Mengnjo, Njodzela Christian; Netongo, Palmer Masumbe; Soniran, Olajoju Temidayo; Chu, Chuo Ennestine; Chiabi, Eugene; Amambua-Ngwa, Alfred; Cheng, Ndong Ignatius (Frontiers in Malaria, 2025)
BackgroundMalaria remains a serious health challenge; thus, the need for continual improvements in treatment regimens and the adoption of new treatment guidelines to enhance case management is vital. We report trends in malaria case management over 15 years at the Jakiri Health Centre in Cameroon, an area that has been plagued with civil unrest since 2016.MethodsData were collected retrospectively from consultation, laboratory, antenatal care (ANC) and prescription registers, and double entered into Excel. Analysis was conducted using SPSS statistics and Microsoft Excel.ResultsA total of 3,800 febrile patients visited the outpatient department (OPD), and patients received 8,324 prescriptions. Of these, 11.6% (964/8324) were anti-malarials, 3.5% (291/8324) were ferrous sulfate (FS), 40.8% (3,396/8324) were antibiotics (AB), and 44.1% (3,673/8324) were analgesics. The antimalarials prescribed were artemisinin-based combination therapies (ACTs) 83.2% (802/964) and quinine (Q) 16.8% (162/964). No ACTs were prescribed between 2006 and 2011. The 5 to <15 years age group received the most proportion of ACTs 42.3% (189/447), followed by the 1 to <5 years age group 31.8% (127/399). Males were more likely to be prescribed ACTs than females were (OR= 1.336, 95% CI 1.141–1.564; p<0.0001). Between 2006 and 2013, the number of quinine prescriptions increased from 17.2% (21/122) in 2006 to a peak of 26.1% (30/115) in 2009. Antibiotic prescription rates were high across all age groups. The prescription of antimalarials to malaria-negative patients was relatively low over time. ACTs were prescribed to all participants attending the ANC who were confirmed malaria-positive. 97.7% of SP was prescribed as intermittent preventive treatment in pregnancy (IPTp) with highest prescription rates observed among women in their third trimester 96.2% (76/79).ConclusionThis study demonstrated that recommended malaria treatment guidelines have been adopted by the Jakiri Health Centre, which has transitioned from quinine as a first-line treatment to ACTs. ACTs were not used in the facility until 2012. Though anti-malaria prescription was largely appropriate, antibiotics and analgesics were highly over prescribed. There is great need for continuous monitoring and refresher training for health workers to enforce adherence to the guidelines.